Mineral-petrochemical wallrock alteration of rocks in Bericul gold-ore deposit (Kuznetsk Alatau) - Kucherenko, Igor Vasilyevich; Zhang Yuxuan; Dolgaya, Tatiana Fedorovna (IOP Publishing, 2015)
The distribution of mineral associations in near-veined zonal propylite-beresite metasomatic columns of mesothermal Bericul gold-ore deposit was analyzed. However, the polymineral composition in the inner (axial and adjacent with it rear) zones is inconsistent to the existing metasomatic column theoretical model. According to Korzhinskii metasomatic zoning theory, implied monomineral (quartz) and binary-mineral (quartz, sericite) compositions are characteristic of axial and rear zones, respectively. In common with above-mentioned facts, the zoning formation of differential component mobility is influenced by two additional factors: counter diffusion of components from fractured fluids into pores and diffusion mechanism of mass transfer it's from pores fluids into fractured of rock-fluid systems.
Keywords: месторождения; Золото; Кузнецкий Алатау; минеральные ассоциации; диффузия